Importance of Strategic Aspect in Project Management: A Literature Critique - Awwal, Mofizul Islam (International Journal of Supply Chain Management, 2014)
The objective of this paper is to provide some critical arguments about project success with a little emphasis on project stakeholders. One of the major findings of this paper is that project can never be successful until and unless it manages to align with its strategic objectives. Moreover project stakeholder’s perception of project success needs to be taken into account while measuring project success. An attempt has been made to relate project success with different stakeholders and their different perception of project success which will help project managers to get a better understanding.